One‐pot Synthesis of Nitrogen and Phosphorus Co‐doped Graphene and Its Use as High‐performance Electrocatalyst for Oxygen Reduction Reaction. Issue 12 (21st September 2015) - Dong, Liye; Hu, Chuangang; Huang, Xianke; Chen, Nan; Qu, Liangti
Abstract: In this study, N, P co‐doped graphene (NPG) was prepared by a one‐step pyrolysis using a mixture of graphene oxide and hexachlorocyclotriphosphazene (HCCP), in which HCCP was used as both the N and P source. Furthermore, it is shown that NPG electrodes, as efficient metal‐free electrocatalysts, have a high onset potential, high current density, and long‐term stability for the oxygen reduction reaction. Abstract : What′s your source : N, P co‐doped graphene (NPG) was prepared by a one‐step pyrolysis using a mixture of graphene oxide and hexachlorocyclotriphosphazene (HCCP), in which the latter was used as both the N and P source. In addition, it is shown that NPG is an efficient electrocatalyst for oxygen reduction reaction.